The Correlation Between Home Reading Habits and Indonesian Language Learning Outcomes in Identifying Main Ideas among Sixth-Grade Students - Irawardi, Irawardi; Sutikno; Rahmat Kartolo (International Journal of Educational Research Excellence, 2026)
This study investigates the correlation between home reading habits and Indonesian language learning outcomes in identifying main ideas in reading texts among sixth-grade students. The research was motivated by observations of low home reading frequency and suboptimal achievement in determining main ideas in Indonesian texts. A quantitative correlational design was employed. The population comprised all 30 sixth-grade students of State Elementary School 357 Natal, Mandailing Natal Regency, in the 2025–2026 academic year; total sampling was applied. Data on home reading habits were collected using a Likert-scale questionnaire, while learning outcomes in determining main ideas were measured through a validated achievement test. Both instruments met requirements of validity and reliability, and data distributions were normal and linear. The results showed a moderate, positive, and statistically significant correlation between home reading habits and Indonesian language learning outcomes (r = 0.5526, t = 3.507, df = 28, p < 0.01). The coefficient of determination indicated that home reading habits accounted for 30.5% of the variance in students’ scores for determining main ideas. These findings underscore the importance of cultivating regular reading practices at home, supported by parents and schools, to enhance reading comprehension—particularly the ability to identify main ideas in Indonesian language texts